How Pure Was Romanian Rugby? Minority, Majority and Extremists in Romanian Interwar Rugby. Issue 11 (2nd September 2022) - Rotar, Marius; Ginghină, Octav
Abstract: One of the most compelling characterisations of interwar Romanian rugby was that it was once a 'pure' sport, played almost exclusively by ethnic Romanians. This issue is important considering the connections between nationalism, sports, and national representation in competitions during the interwar period in Romania. For Romanian rugby, the issue had also been raised in the 1930s when, in the context of the controversies surrounding the Romanization of the national football team, the national rugby team was cited as an example of a situation in which results or field losses were irrelevant because those who represented Romania were 'pure' Romanians. The purpose of this article is to quantitatively and qualitatively analyse the ethnic 'purity' of Romanian rugby, from the national team to the teams which played in the first division. An analysis of the rugby minority and the extremist teams (Macabbi Bucharest, Legiunea Sportivă Bucharest) will be undertaken, as will the changes in Romanian rugby during the National Legionary State. This article proves the falseness of the purity idea of Interwar Romanian rugby, using content analysis and explaining this in the context of that epoch.